Eocene – Late Miocene Tectonostratigraphy of Bima Field in Northwest Java Basin - Natasia, Nanda; Alfadli, Muhammad Kurniawan; Syafri, Ildrem (Journal of Geological Sciences and Applied Geology, 2017)
This study aim to understand the tectonostratigraphy of Bima Field from Basement forming in Eocene to Late Miocene Interval based on seismic observation. Regional structural analysis of the Bima Field and surrounding area was conducted using integration 2D seismic lines and existing wells. The main purpose of the analysis is to describe structural pattern and style in the study area in relation to regional tectonic of the North-West Java Basinal area. The results of structural mapping using regional 2D seismic data controlled by numbers of wells indicates study area is mostly located along NNE-NSW trending basement high structures (Figure 3). Structural development of the study area is dominated by series of normal faults system with some locally observed folds. In many seismic sections, faults geometry characterized by high to moderate dips. This specific geometry often interpreted as half graben and horst structures resulting from Eocene rifting. The structural geology of Bima field can be observed clearly at the WNW-ESE seismic line. It was dominated by N-S trending Normal fault that was probably related to the Eocene rifting which occurred predominantly at the west part of the study area. The main fault, occurred toward to the west, formed the half graben system which cut from basement to Parigi formation. However, others that placed at central part only cut the basement. The pre-Baturaja Sediment can be divided into two packages, which are syn-rift package and quiescence package while the post-Baturaja interval is the late post rift (sag) package.